2009
DOI: 10.1002/clen.200900158
|View full text |Cite
|
Sign up to set email alerts
|

Use of Agro‐Industrial Wastes for Removal of Basic Dyes from Aqueous Solutions

Abstract: The biosorption potential of three different agro-industrial waste materials of lignocellulosic origin, i. e., coir pith (CP), sawdust (SD) and sugarcane fiber (SF), is investigated in the case of basic dyes, i. e., crystal violet (CV) and rhodamine B (RB). The uptake of dyes from aqueous solutions is found to be rapid when using these candidate biosorbents. The application of various kinetic models reveals good correlation of a pseudo-second order kinetics model with the experimental data. Equilibrium adsorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(44 citation statements)
references
References 43 publications
3
41
0
Order By: Relevance
“…The usage of agro-industrial wastes for the removal of basic dyes from aqueous solutions was discussed [70]. Experimental data showed that all the adsorbents used, which included coir pith, sawdust and sugarcane fiber, were effective for the removal of Crystal Violet and Rhodamine B and their adsorption capacities are comparable with other reported adsorbents.…”
Section: Sorption Processmentioning
confidence: 90%
“…The usage of agro-industrial wastes for the removal of basic dyes from aqueous solutions was discussed [70]. Experimental data showed that all the adsorbents used, which included coir pith, sawdust and sugarcane fiber, were effective for the removal of Crystal Violet and Rhodamine B and their adsorption capacities are comparable with other reported adsorbents.…”
Section: Sorption Processmentioning
confidence: 90%
“…It is usually necessary to carry out experimental studies using several variables to test data in order to confirm whether the mechanism is film diffusion, diffusion sorption or a combination of these processes (Ho et al 2000). Three kinetic models (Table 9) are widely used to describe the adsorption of dye by MPSs: (i) pseudo-first-order kinetic model (Lagergren model) (Parab et al 2009); (ii) pseudo-second-order kinetic model (Ho and McKay model) (Mahmoodi et al 2011); (iii) intraparticle diffusion model (Webber and Morris model) (Qin et al 2009). (Yan et al 2006b) Red X-3B Langmuir 1.10 - (Yan et al 2006b) Yellow X-RG Langmuir 2.25 - (Yan et al 2006b) Sometimes the pseudo-first-order model is not a good fit over the whole range of contact times and fails to predict the amount of dye adsorbed.…”
Section: Kineticmentioning
confidence: 99%
“…However, it is very expensive and has high operating cost [8,9]. Therefore, in recent years, considerable attention has been devoted to the study of different types of low cost materials such as oil shale ash [4], acid treated data stones [8], chestnut shell [10], watermelon peels [11], wood charcoal [12], fly ash [13], modified rice husk [14], surfactant-modified coir pith [15], agro-industrial wastes [16], wood fly ash [17], tamarind fruit shell [18], peel of Cucumis sativa fruit [19], etc., for the adsorption of pollutants from water. Nevertheless, the literature on this subject is still inadequate, and more studies are required to find low cost adsorbents for removal of pollutants from water.…”
Section: Introductionmentioning
confidence: 99%